Correlation and path coefficient analysis of body weight and morphometric traits of two exotic genetic groups of ducks in Nigeria (Bangladesh Journal of Animal Science, 2015)
The study aimed at describing objectively the interdependence between body weight (BWT) and morphometric traits in Khaki Campbell and Pekin ducks using multivariate path analysis technique. Measurements were taken on one hundred and ninety seven (197) randomly selected 10-week old Khaki Campbell and Pekin ducks, respectively in Plateau State, Nigeria. The birds were reared on deep litter in a semi-intensive system where they were kept in a fenced area provided with water ponds and locked up in the poultry house during the night. The body parts measured were, body length (BDL); thigh length (THL); thigh circumference (THC); breast circumference (BTC); bill length (BLL); neck length (NKL); neck circumference (NKC); shank length (SHL); shank width (SHW); total leg length (TLL) and wing length (WL). General linear model was used to study genotype and sex effects. Pekin ducks had a superior advantage (p